PRINCIPAL'S MANAGERIAL STRATEGY: OPTIMIZING THE ROLE OF THE LEARNING COMMUNITY IN IMPROVING THE QUALITY OF LEARNING AT SDN 1 KALIPANG - Sugiharti Sugiharti; ngurah ayu nyoman murniati; muhamad Prayito (SOSIOEDUKASI, 2025)
SDN 1 Kalipang has actively implemented Learning Communities, resulting in improved performance on the educational report card over the last three years. This study aims to describe and analyze the principal’s strategic and operational roles in managing Learning Communities to improve learning quality at SDN 1 Kalipang. Using a qualitative case study design, data were collected through in-depth interviews with principals and teachers, observations of Learning Community activities, and documentation analysis. The findings indicate that the principal demonstrates comprehensive leadership. Strategically, the principal positions Learning Communities as a priority program aligned with the school’s vision. Operationally, the principal facilitates collaborative routines, ensures resource allocation, and creates a supportive culture for teachers. The study concludes that the principal’s managerial strategy—both strategic and operational—significantly enhances the effectiveness of Learning Communities as a collaborative mechanism for improving learning quality.